PERANCANGAN BUKU EDUKASI CERITA BERGAMBAR BERBASIS BAHASA INGGRIS UNTUK ANAK USIA 9 – 12 TAHUN - RUDY ADITYA SYAHRUL, San Ahdi, M.Sn., M.Ds. Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of this design is the introduction of nature, culture, and character of the people of Alahan Panjang, Solok Regency, which are promoted for publication through visuals in the form of English-based story books for children aged 9-12 years and fostering motivation to read children's interest in English and are expected to help teaching staff in schools and agencies in the method of learning English.The design of this book is through the method (Glass Box), which means rational thinking that objectively and systematically examines things logically, free from thoughts and irrational (irrational) considerations, such as sentiments and tastes. This method seeks to find facts and factual causes that underlie the occurrence of events and then try to find alternative solutions to problems that arise by analyzing 5W + 1H data (what, who, where, when, why and how) to find solutions to the problems encountered.The design of the main media produced a picture book with the title Jaka the Son of Durhaka as well as several supporting media such as posters, x-banners, stickers, totebags, pencil boxes, pins, drink bottles and picture books to support the main media.Key Words : Book, Comic, Language